Chronic Thromboembolic Pulmonary Hypertension after Pulmonary Embolism, Thrombolysis, Catheter Fragmentation, and Embolectomy - Wiedenroth, Christoph B.; Guth, Stefan; Rolf, Andreas; Mayer, Eckhard (The Thoracic and Cardiovascular Surgeon Reports, 2014)
A 21-year-old male patient with massive acute pulmonary embolism was treated by thrombolysis, interventional thrombus fragmentation, and surgical pulmonary embolectomy. Within the following 2 years, the patient developed progressive dyspnea at exertion. Chronic thromboembolic pulmonary hypertension was diagnosed by right-heart catheter, VQ scan, magnetic resonance, and conventional pulmonary angiography. A normalization of the patient's exercise capacity and pulmonary hemodynamics could be achieved by pulmonary endarterectomy and patch reconstruction of the right main pulmonary artery.
Keywords: pulmonary embolism; chronic thromboembolic pulmonary hypertension; pulmonary endarterectomy